Design and sensitivity of the Radio Neutrino Observatory in Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Buitink, S.; Carter, K.; Clark, B. A.; Connolly, A.; Dasgupta, P.; et al. (Journal of Instrumentation, 2021)
This article presents the design of the Radio Neutrino Observatory Greenland (RNO-G) and discusses its scientific prospects. Using an array of radio sensors, RNO-G seeks to measure neutrinos above 10 PeV by exploiting the Askaryan effect in neutrino-induced cascades in ice. We discuss the experimental considerations that drive the design of RNO-G, present first measurements of the hardware that is to be deployed and discuss the projected sensitivity of the instrument. RNO-G will be the first production-scale radio detector for in-ice neutrino signals.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Large detector systems for particle and astroparticle physics; Neutrino detectors

Improving sensitivity of the ARIANNA detector by rejecting thermal noise with deep learning - Anker, A.; Baldi, P.; Barwick, S. W.; Beise, J.; Besson, D. Z.; Bouma, Sjoerd; Cataldo, Maddalena; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hallmann, S.; et al. (Journal of Instrumentation, 2022)
The ARIANNA experiment is an Askaryan detector designed to record radio signals induced by neutrino interactions in the Antarctic ice. Because of the low neutrino flux at high energies (Eν > 1016 eV), the physics output is limited by statistics. Hence, an increase in sensitivity significantly improves the interpretation of data and offers the ability to probe new parameter spaces. The amplitudes of the trigger threshold are limited by the rate of triggering on unavoidable thermal noise fluctuations. We present a real-time thermal noise rejection algorithm that enables the trigger thresholds to be lowered, which increases the sensitivity to neutrinos by up to a factor of two (depending on energy) compared to the current ARIANNA capabilities. A deep learning discriminator, based on a Convolutional Neural Network (CNN), is implemented to identify and remove thermal events in real time. We describe a CNN trained on MC data that runs on the current ARIANNA microcomputer and retains 95% of the neutrino signal at a thermal noise rejection factor of 105, compared to a template matching procedure which reaches only 102 for the same signal efficiency. Then the results are verified in a lab measurement by feeding in generated neutrino-like signal pulses and thermal noise directly into the ARIANNA data acquisition system. Lastly, the same CNN is used to classify cosmic-rays events to make sure they are not rejected. The network classified 102 out of 104 cosmic-ray events as signal.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Cherenkov detectors; Neutrino detectors; Real-time monitoring

In situ, broadband measurement of the radio frequency attenuation length at Summit Station, Greenland - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Besson, D.; Bishop, A.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Cataldo, Maddalena; Clark, B. A.; Curtis-Ginsberg, Z.; Connolly, A.; et al. (Journal of Glaciology, 2022)
Over the last 25 years, radiowave detection of neutrino-generated signals, using cold polar ice as the neutrino target, has emerged as perhaps the most promising technique for detection of extragalactic ultra-high energy neutrinos (corresponding to neutrino energies in excess of 0.01 Joules, or 10(17) electron volts). During the summer of 2021 and in tandem with the initial deployment of the Radio Neutrino Observatory in Greenland (RNO-G), we conducted radioglaciological measurements at Summit Station, Greenland to refine our understanding of the ice target. We report the result of one such measurement, the radio-frequency electric field attenuation length L-alpha. We find an approximately linear dependence of L-alpha on frequency with the best fit of the average field attenuation for the upper 1500 m of ice: < L-alpha > = ((1154 +/- 121) - (0.81 +/- 0.14) (v/MHz)) m for frequencies v is an element of [145 - 3501 MHz.
CRIS-Team WoS Importer:2022-06-10

Measuring the polarization reconstruction resolution of the ARIANNA neutrino detector with cosmic rays - Anker, A.; Baldi, P.; Barwick, S. W.; Beise, J.; Besson, D. Z.; Bouma, Sjoerd; Cataldo, Maddalena; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hallmann, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
The ARIANNA detector is designed to detect neutrinos with energies above 1017 eV. Due to the similarities in generated radio signals, cosmic rays are often used as test beams for neutrino detectors. Some ARIANNA detector stations are equipped with antennas capable of detecting air showers. Since the radio emission properties of air showers are well understood, and the polarization of the radio signal can be predicted from the arrival direction, cosmic rays can be used as a proxy to assess the reconstruction capabilities of the ARIANNA neutrino detector. We report on dedicated efforts of reconstructing the polarization of cosmic-ray radio pulses. After correcting for difference in hardware, the two stations used in this study showed similar performance in terms of event rate and agreed with simulation. Subselecting high quality cosmic rays, the polarizations of these cosmic rays were reconstructed with a resolution of 2.5° (68% containment), which agrees with the expected value obtained from simulation. A large fraction of this resolution originates from uncertainties in the predicted polarization because of the contribution of the subdominant Askaryan effect in addition to the dominant geomagnetic emission. Subselecting events with a zenith angle greater than 70° removes most influence of the Askaryan emission, and, with limited statistics, we found the polarization uncertainty is reduced to 1.3° (68% containment).
CRIS-Team Scopus Importer:2022-05-13
Keywords: cosmological neutrinos; neutrino astronomy; neutrino detectors; ultra high energy photons and neutrinos

Probing the angular and polarization reconstruction of the ARIANNA detector at the South Pole - Anker, A.; Barwick, S. W.; Bernhoff, H.; Besson, D. Z.; Bingefors, N.; García-Fernández, D.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Klein, S. R.; Kleinfelder, S. A.; et al. (Journal of Instrumentation, 2020)
The sources of ultra-high energy (UHE) cosmic rays, which can have energies up to 1020 eV, remain a mystery. UHE neutrinos may provide important clues to understanding the nature of cosmic-ray sources. ARIANNA aims to detect UHE neutrinos via radio (Askaryan) emission from particle showers when a neutrino interacts with ice, which is an efficient method for neutrinos with energies between 1016 eV and 1020 eV. The ARIANNA radio detectors are located in Antarctic ice just beneath the surface. Neutrino observation requires that radio pulses propagate to the antennas at the surface with minimum distortion by the ice and firn medium. Using the residual hole from the South Pole Ice Core Project, radio pulses were emitted from a transmitter located up to 1.7 km below the snow surface. By measuring these signals with an ARIANNA surface station, the angular and polarization reconstruction abilities are quantified, which are required to measure the direction of the neutrino. After deconvolving the raw signals for the detector response and attenuation from propagation through the ice, the signal pulses show no significant distortion and agree with a reference measurement of the emitter made in an anechoic chamber. Furthermore, the signal pulses reveal no significant birefringence for our tested geometry of mostly vertical ice propagation. The origin of the transmitted radio pulse was measured with an angular resolution of 0.37◦ indicating that the neutrino direction can be determined with good precision if the polarization of the radio-pulse can be well determined. In the present study we obtained a resolution of the polarization vector of 2.7◦. Neither measurement show a significant offset relative to expectation.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Data analysis; Neutrino detectors; Performance of High Energy Physics Detectors; Systematic effects

Radiofrequency ice dielectric measurements at Summit Station, Greenland - Aguilar, Juan Antonio; Allison, Patrick; Besson, Dave; Bishop, Abby; Botner, Olga; Bouma, Sjoerd; Buitink, Stijn; Cataldo, Maddalena; Clark, Brian A.; Couberly, Kenny; Curtis-Ginsberg, Zach; Dasgupta, Paramita; et al. (Journal of Glaciology, 2023)
We recently reported on the radio-frequency attenuation length of cold polar ice at Summit Station, Greenland, based on bi-static radar measurements of radio-frequency bedrock echo strengths taken during the summer of 2021. Those data also allow studies of (a) the relative contributions of coherent (such as discrete internal conducting layers with sub-centimeter transverse scale) vs incoherent (e.g. bulk volumetric) scattering, (b) the magnitude of internal layer reflection coefficients, (c) limits on signal propagation velocity asymmetries ('birefringence') and (d) limits on signal dispersion in-ice over a bandwidth of ∼100 MHz. We find that (1) attenuation lengths approach 1 km in our band, (2) after averaging 10 000 echo triggers, reflected signals observable over the thermal floor (to depths of ∼1500 m) are consistent with being entirely coherent, (3) internal layer reflectivities are ≈-60-70 dB, (4) birefringent effects for vertically propagating signals are smaller by an order of magnitude relative to South Pole and (5) within our experimental limits, glacial ice is non-dispersive over the frequency band relevant for neutrino detection experiments.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Arctic glaciology; ice physics; radio-echo sounding

Reconstructing the neutrino energy for in-ice radio detectors: A study for the Radio Neutrino Observatory Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Carter, K.; Cataldo, Maddalena; Clark, B. A.; et al. (European Physical Journal C: Particles and Fields, 2022)
Since summer 2021, the Radio Neutrino Observatory in Greenland (RNO-G) is searching for astrophysical neutrinos at energies > 10 PeV by detecting the radio emission from particle showers in the ice around Summit Station, Greenland. We present an extensive simulation study that shows how RNO-G will be able to measure the energy of such particle cascades, which will in turn be used to estimate the energy of the incoming neutrino that caused them. The location of the neutrino interaction is determined using the differences in arrival times between channels and the electric field of the radio signal is reconstructed using a novel approach based on Information Field Theory. Based on these properties, the shower energy can be estimated. We show that this method can achieve an uncertainty of 13% on the logarithm of the shower energy after modest quality cuts and estimate how this can constrain the energy of the neutrino. The method presented in this paper is applicable to all similar radio neutrino detectors, such as the proposed radio array of IceCube-Gen2.
CRIS-Team Scopus Importer:2022-03-04

Solar flare observations with the Radio Neutrino Observatory Greenland (RNO-G) - Agarwal, S.; Aguilar, J. A.; Ali, S.; Allison, P.; Betts, M.; Besson, D.; Bishop, A.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Cataldo, Maddalena; Clark, B. A.; et al. (Astroparticle Physics, 2025)
The Radio Neutrino Observatory – Greenland (RNO-G) seeks discovery of ultra-high energy neutrinos from the cosmos through their interactions in ice. The science program extends beyond particle astrophysics to include radioglaciology and, as we show herein, solar observations, as well. Currently seven of 35 planned radio-receiver stations (24 antennas/station) are operational. These stations are sensitive to impulsive radio signals with frequencies between 80 and 700 MHz and feature a neutrino trigger threshold for recording data close to the thermal floor. RNO-G can also trigger on elevated signals from the Sun, resulting in nanosecond resolution time-domain flare data; such temporal resolution is significantly shorter than from most dedicated solar observatories. In addition to possible RNO-G solar flare polarization measurements, the Sun also represents an extremely useful above-surface calibration source. Using RNO-G data recorded during the summers of 2022 and 2023, we find signal excesses during solar flares reported by the solar-observing Callisto network and also in coincidence with ∼2/3 of the brightest excesses recorded by the SWAVES satellite. These observed flares are characterized by significant time-domain impulsivity. Using the known position of the Sun, the flare sample is used to calibrate the RNO-G absolute pointing on the radio signal arrival direction to sub-degree resolution. We thus establish the Sun as a regularly observed astronomical calibration source to provide the accurate absolute pointing required for neutrino astronomy.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Calibration; Radio telescopes; Solar flares; UHE neutrinos